KERJASAMA INDONESIA-FIJI DALAM KERANGKA SOUTH-SOUTH COOPERATION (SSC): Pemberdayaan Industri Kerajinan Kulit Kerang Periode 2014-2017 - Maulana Arbi Irsyad, (2020)
Fiji is archipelagic countries and has tropical climate in South-Pacific region and yet still developing countries. Fiji is Categorized as South-Nation and still needs to develop its economy to fulfill its national welfare. South-South Cooperation framework is the form of cooperation between South-Nations to help the economic development of another South-Nations. As fellow South-Nations and has many similar characteristic, Indonesia trying to help Fiji to develop its economy through technical cooperation of seashell craft training under South-South Cooperation Framework. This research examine about technical cooperation of seashell crafting under South-South Cooperation framework as the factor that encouraging Fiji's Economic Development. This Research using Bilateral Relation, South-South Cooperation and Technical Assistance as the main theories and concepts. This Study using primer and secondary data with qualitative-descriptive approach to explaining and describing the topic of this research, also using inductive approach to analyse this research. Beginning with the analysis of South-South Cooperation between Indonesia and Fiji. The analysis continued with the seashell-craft training programs and examine about technical cooperation of seashell-craft training impact in Fiji, including the explanation about how this technical cooperation as the factor that encouraging of economic development in Fiji.